Pengaruh Compound Annual Growth Rate, Drawdown, Expense Ratio, Dan Total Asset Under Management Terhadap Pengambilan Keputusan Berinvestasi Pada Dana Reksa - Mohamad Soedarman; Putrin Mar’ah Afifah; Abdul Kadir Usri (Universitas Riau Kepulauan, 2022)
This study aims to determine the effect of compound annual growth rate, drawdown, expense ratio, and total asset under management on student investment decisions in mutual fund products. The type of research used in this study is non-case quantitative research. The sample in this study found 92 samples obtained from filling out questionnaires via google forms to students who are belonging to the investment group on telegram social media. The sampling method used is a purposive sampling method with the criteria that students are active, interested in investing in mutual funds, and have invested in mutual funds. Based on the regression analysis, the compound annual growth rate and total asset under management have a positive and significant effect on student investment decisions in mutual fund products, while the drawdown and expense ratio variables have no effect on student investment decisions in mutual fund products.